(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Md Noordin NA, Zainudin NAIM, Khairuddin NH, Yusof MT. 2024. Species diversity and ecological roles of macrofungi in Lentang Forest Reserve, Pahang, Malaysia. Biodiversitas 25: 2615-2622. Macrofungi are high-value forest components with functionally significant roles in the forest ecosystem, however, fungi and their functions remain among the least studied. Therefore, this study aims to unravel the current diversity of macrofungi in Lentang Forest Reserve, located in Pahang, Malaysia to provide data for comparison with other ecosystems. Macrofungal sporocarps were collected from selected sites using convenience sampling. A total of 332 sporocarps were identified based on morphological and Internal Transcribed Spacer (ITS) sequence analysis. Ascomycota and Basidiomycota predominated in the Lentang Forest Reserve, with 28 genera representing 8 families were successfully identified. A Shannon diversity index of 0.454 indicated high fungal diversity in the sampling location. Microclimatic changes do not significantly affect fungal orders and substrates across the studied sites, suggesting random chance rather than systematic influences. The samples of Polyporales had the highest amounts, which showed that microclimate factors affected the make-up of the fungal fruiting community. In harsh microclimates, tough-fleshed fruit bodies were more common. The Agaricomycetes class exhibited the highest species presence, accounting for 89.09% of the identified species. The findings of this study can serve as a valuable checklist for future research on fungal distribution in tropical regions and will significantly contribute to biodiversity conservation efforts.